Effectiveness of greenhouse-gas Emission Trading Schemes implementation: a review on legislations - Villoria-Sáez, P.; Tam, V.; Río Merino, M.; Viñas Arrebola, C.; Wang, Xiangyu (Elsevier, 2016)
Due to the severe problems caused by global warming, controlling greenhouse-gas emissions has become an emerging topic around the world. This situation has led to the implementation of legislations, forcing companies to implement innovations and strategies to prevent and reduce carbon emissions. Nevertheless, the effectiveness of implementing these strategies and the estimation to fulfill Kyoto Protocol's 2020 target Emission Trading Schemes needs to be further analysed and discussed. This paper reviews the existing greenhouse-gas-emission legislations, as well as carbon offset programs worldwide. A detailed analysis on carbon emissions trends related to emissions penalties is shown for six major countries. The optimal penalty for emissions trading schemes is also analyzed and discussed in this paper. Future changes that could be made to the existing programs for enhancing their effectiveness are also suggested. It was found that carbon emissions decreased around 1.58% per year since Emission Trading Schemes implementation. Around 23.43% of CO2 reduction can be reached after 10 years of Emission Trading Schemes implementation, compared to the trend when Emission Trading Schemes was not implemented. Despite Emission Trading Schemes implementation is extremely recent, based on the existing data a first estimation of the optimal penalty in achieving the maximum carbon reduction it was found around US$90.22 per tonne. However, as the implementation period of Emission Trading Schemes is still limited for most countries, it is necessary to explore similar analysis as future work.